2018
DOI: 10.1111/jtsb.12175
|View full text |Cite
|
Sign up to set email alerts
|

Social deontics: A nano‐level approach to human power play

Abstract: The notion of "deontic rights"-the capacity of an individual to determine action-is described as a tool to analyze human power plays in the turn-by-turn unfolding of social interaction. Drawing on various bodies of literature, the paper portrays the organization of the adjacency-pair sequence as the key locus of negotiation over deontic rights. How such negotiations happen in practice is also considered. Two deontic patterns instantiating themselves in sequential relations-deontic congruence and deontic incong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 99 publications
3
62
0
5
Order By: Relevance
“…The Jamaican mothers in this study overwhelmingly expressed their disapproval of their children’s resistance, which is consistent with previous findings of the authoritarian nature of Jamaican parents (Smith and Mosby, 2003). However, this finding can be contrasted with North American studies which found that middle class mothers tended to tolerate resistance as a normative and acceptable expression of their children’s developing autonomy (Kuczynski and Hildebrandt, 1997; Kuczynski et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Jamaican mothers in this study overwhelmingly expressed their disapproval of their children’s resistance, which is consistent with previous findings of the authoritarian nature of Jamaican parents (Smith and Mosby, 2003). However, this finding can be contrasted with North American studies which found that middle class mothers tended to tolerate resistance as a normative and acceptable expression of their children’s developing autonomy (Kuczynski and Hildebrandt, 1997; Kuczynski et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Micro-level analyses of parent–child conversations suggest that power, authority, and the right for self-determined action are negotiated in a subtle, barely perceptible way as very young children deflect, evade, and challenge parental requests and claims to authority during moment to moment interchanges (Kent, 2012; Stevanovic, 2018). At a more molar level, analyses of less frequent parent–child conflict occasioned by children’s non-compliant responses to parental demands, standing rules, and prohibitions have been regarded as social strategies whereby children attempt to influence parents to drop or modify their demands (Kuczynski et al, 1987; Kuczynski and Kochanska, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This was also the case in our data, in which all the discrepancies analyzed were implicit, occurring below the surface level of the interaction. More specifically, although the participants basically expressed agreement with each other’s views, simply building and elaborating on them in and through the turn-by-turn unfolding of interaction, they displayed differences in their orientations towards how knowledgeable they were, or were expected to be [ 78 ] and who was to define what should and what should not be done [ 79 ]. Such negotiations consist of participants dealing with each other’s turns, not entirely on their own terms, but in ways that slightly deviate from and refrain from appreciating the full interactional import of the earlier talk [ 40 ] (p. 260).…”
Section: Discussionmentioning
confidence: 99%
“…measure patients' attachment to providers, found fear of rejection (and therefore cautious behavior), and feelings of being humiliated or shamed, as strong predictors of weak attachment (20). Surveys are indicators of what is important for patients, but we need detailed interaction studies to understand why patients are left with negative experiences (we must presume that this is not what physicians want to achieve).…”
Section: Discussionmentioning
confidence: 99%